Characterization of modern reefs using the Atlantic and Gulf Rapid Reef Assessment (AGRRA) protocol and digitized aerial photographs, Tobago Cays Marine Park, St. Vincent and the Grenadines. - Deschamps, Alice. (University of Ottawa (Canada), 2000)
A digital thematic map of the shallow marine habitats surrounding the Tobago Cays and the Horseshoe Reef was created using a low-cost remote sensing methodology. Colour aerial photographs were selected because of their high spatial resolution and availability. The aerial photographs were scanned, georeferenced, rectified (ground control points and a second order polynomial) and mosaicked to cover the entire study arm. Benthic classes were derived and described objectively using agglomerative hierarchical classification of field data. Supervised classification of the Tobago Cays was obtained using this field derived classification. The final thematic map comprises 8 classes (mixed live coral community, dead coral substratum with mixed algae, seagrass dominated, macro algae dominated, sand dominated, rubble dominated, deep water and beach sands) with an overall accuracy of 87% and a Kappa and Tau coefficients of 85%. Producer and user accuracies of individual classes range between 53% and 100%. (Abstract shortened by UMI.)
Keywords: Geology.